Outcomes Analysis and Quality Improvement in Children With Congenital and Acquired Cardiovascular Disease. (August 2016) - Jeffries, Howard E.; Gaies, Michael G.
Abstract : Objectives: In this review, the current state of outcomes analysis and quality improvement in children with acquired and congenital cardiovascular disease will be discussed, with an emphasis on defining and measuring outcomes and quality in pediatric cardiac critical care medicine and risk stratification systems. Data Source: MEDLINE and PubMed Conclusion: Measuring quality and outcomes in the pediatric cardiac critical care environment is challenging owing to many inherent obstacles, including a diverse patient mix, difficulty in determining how the care of the ICU team contributes to outcomes, and the lack of an adequate risk-adjustment method for pediatric cardiac critical care patients. Despite these barriers, new solutions are emerging that capitalize on lessons learned from other quality improvement initiatives, providing opportunities to build upon previous successes.